2022
DOI: 10.1093/jxb/erac134
|View full text |Cite
|
Sign up to set email alerts
|

Liverwort oil bodies: diversity, biochemistry, and molecular cell biology of the earliest secretory structure of land plants

Abstract: Liverworts are known for their large chemical diversity. Much of this diversity is synthesized and enclosed within the oil bodies (OB), a synapomorphy of the lineage. OB contain the biosynthetic enzymes to produce and store large quantities of sesquiterpenoids and other compounds while limiting their cytotoxicity. Recently, there were important biochemical and molecular discoveries related to OB formation, diversity and biochemistry that allows the comparison with other secretory structures of land plants in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 112 publications
0
14
0
Order By: Relevance
“…As a note, the lipid droplets mentioned here in this study are not what had been described as “oil body” in liverworts. Lipid droplets are present in almost all green plants accumulating compounds that are not soluble in the aqueous phase, and oil bodies are present only in liverwort, storing large quantities of toxic sesquiterpenoids [ 17 , 52 , 53 , 54 , 55 ]. Lipid droplets are subcellular organelles of monolayer membranes with a diameter of about 0.5–2 µm, while oil bodies are an endocrine structure surrounded by a lipid bilayer membrane [ 13 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a note, the lipid droplets mentioned here in this study are not what had been described as “oil body” in liverworts. Lipid droplets are present in almost all green plants accumulating compounds that are not soluble in the aqueous phase, and oil bodies are present only in liverwort, storing large quantities of toxic sesquiterpenoids [ 17 , 52 , 53 , 54 , 55 ]. Lipid droplets are subcellular organelles of monolayer membranes with a diameter of about 0.5–2 µm, while oil bodies are an endocrine structure surrounded by a lipid bilayer membrane [ 13 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid droplets are present in almost all green plants accumulating compounds that are not soluble in the aqueous phase, and oil bodies are present only in liverwort, storing large quantities of toxic sesquiterpenoids [ 17 , 52 , 53 , 54 , 55 ]. Lipid droplets are subcellular organelles of monolayer membranes with a diameter of about 0.5–2 µm, while oil bodies are an endocrine structure surrounded by a lipid bilayer membrane [ 13 , 55 ]. The size of small oil bodies is 2–5 × 3–9 µm on average, and the diameter of large oil bodies can reach 70 µm [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to test the power of MBEX to gain biological insights, we focused on genes associated with oil bodies in M. polymorpha. Oil bodies in liverworts, which are distinct from 'oil bodies' in angiosperms, are a synapomorphic feature of liverworts (Romani et al, 2022). In M. polymorpha, oil body cells are scattered in the plant body (Fig.…”
Section: Case Study: An Oil Body-specific Gene Networkmentioning
confidence: 99%
“…In the liverwort Marchantia polymorpha, one oil body is formed in a specific idioblastic cell, referred to as the oil body cell. Recent analyses have revealed that at least two key transcription factors, MpC1HDZ and MpERF13, mediate oil body cell differentiation and oil body development in M. polymorpha (Kanazawa et al, 2020;Romani et al, 2020Romani et al, , 2022. The Qa-SNARE protein MpSYP12B, which is homologous to the PM-resident MpSYP13B protein, is targeted to the oil-body membrane (Kanazawa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The liverwort oil body is a striking example of a lineage-unique organelle specifically acquired by distinctive eukaryotic lineages during evolution. Notably, the liverwort oil body is an organelle independent from the oil body in seed plants (also known as the oleosome or lipid body) in regard to its origin or function; the liverwort oil body is surrounded by the phospholipid bilayer membrane similar to endomembrane organelles and probably acts in chemical protection against microbes and herbivores, whereas the seed plant oil body is surrounded by a lipid monolayer derived from the ER and accumulates neutral lipids as energy sources ( Huang, 1992 ; He et al, 2013 ; Huang et al, 2013 ; Kanazawa et al, 2020 ; Romani et al, 2020 , 2022 ). The morphology and distribution patterns of the liverwort oil body, such as the shape, color, and number in a cell, vary depending on the liverwort species and have thus been used as an index for taxonomically classifying liverworts ( Müller, 1939 ; He et al, 2013 ; Romani et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%